Primary meningococcal septic arthritis with multiple native joint involvement. (8th May 2018) - Boyle, Connor; Howard, Thomas; Griffith, David; Cowie, Jonathan
Abstract : A previously healthy 18-year-old woman presented with an acutely painful, swollen right ankle joint, with similar symptoms subsequently developing in the right hip and right wrist. Microbiological samples from the ankle aspirate grew Neisseria meningitidis . She had had no preceding clinical symptoms of meningitis or previous contact with a patient with meningitis. She was treated with intravenous antibiotics and surgical drainage. On follow-up, her symptoms had resolved, inflammatory markers had returned to normal and she has no long-term sequelae of septic arthritis. Primary meningococcal septic arthritis in the adult population is extremely uncommon, and makes up approximately 1% of all cases of primary septic arthritis.